Greening of capitalism : how Asia is driving the next great transformation - Mathews, John A. (John Alwyn), 1946- (Stanford University Press, 2015)
As China, India, and other industrializing giants grow, they are confronted with an inconvenient truth: They cannot rely on the conventions of capitalism as we know them today. Western industrialism has achieved miracles, promoting unprecedented levels of prosperity and raising hundreds of millions out of poverty. Yet, if allowed to proceed unencumbered, this paradigm will do irreversible harm to the planet. By necessity, a new approach to environmentally conscious development is already emerging in the East, with China leading the way. Positioning its argument against zero-growth advocates and.